Nephrectomy – A study of recent trends in a high-volume tertiary care center, exploring the need for screening and preventive strategies - Vyas, Ankit; Singh, Kamlesh; Rochlani, Tarun; Bhujbal, Sachin; Patil, Bhushan; Patwardhan, Sujata (Asian Journal of Medical Sciences, 2022)
Background: Nephrectomy being one of the most commonly performed procedures, a retrospective study and analysis was done to evaluate, the scope for screening and timely preventive measures that could help to reduce the need for nephrectomy. Aims and Objectives: The aim of the study was to study indications, demographic-details, clinical-presentations, time delay, comorbidities, operative procedures, and complications of patients undergoing nephrectomies. The study was to identify the high risk groups, assess for feasibility for screening measures, and formulate strategies for nephrectomy prevention for benign etiologies. Materials and Methods: A retrospective study was done on medical records of 220 consecutive nephrectomies from June 2018 to June 2020. Results: Out of 220 nephrectomies, 68% were performed for benign conditions, 17% for malignant etiology, and 15% were donor nephrectomies. In the benign group, the most common etiology was renal stones (44.54%), followed by pelvic ureteric junction obstruction (12.72 %), and renal tuberculosis (6.81%). The most common clinical presentations were flank pain (80%), followed by lower urinary tract symptoms (22%), dysuria (25%), hematuria (15%), and fever (7%). In the malignant group, the most common etiology was renal cell carcinoma (14.09%). The most common clinical presentations were flank pain (90%) followed by hematuria (67%). Overall, 24% of the patients presented with acute kidney injury. A pre-operative intervention such as DJ stenting and percutaneous nephrostomy insertion was performed in 13% and 9% of patients, respectively. A laparoscopic approach was used in 76% of the patients out of which 10% were converted to open procedures. Partial nephrectomy was performed in 3% of patients. Conclusion: There is a difference in nephrectomy indications between Western countries and India, where 68% of nephrectomies are performed for benign conditions especially calculus disease. Nephrectomy for calculus disease is potentially preventable and public education in the form of posters, media and the involvement of the community medicine department could be helpful.